Octave Mirbeau : Two Plays - Business Is Business & Charity. - Hand, Richard J. (Intellect, 2011)
Octave Mirbeau was born in Trévières, Normandy, on 16 February 1848. He had a quiet childhood, which seemingly came to an abrupt end when he was sent to a Jesuit college at Vannes in 1859. The next four years were a miserable experience for the young Mirbeau, and the barbarity, tyranny and snobbery he encountered there - which seemed to him a microcosm of French society - would never be far from his writing for the rest of his life. Mirbeau registered to study law at university in 1866 but in 1868 would claim that 'he had been eating nothing and smoking up to 180 pipes of opium a day' (Levi, 1.